2005
DOI: 10.1592/phco.2005.25.6.817
|View full text |Cite
|
Sign up to set email alerts
|

Peak Antifactor Xa Activity Produced by Dalteparin Treatment in Patients with Renal Impairment Compared with Controls

Abstract: No meaningful difference in peak antifactor Xa activity was found between patients with renal impairment and control subjects. To the extent that peak antifactor Xa levels can be used as markers for adjusting doses of dalteparin, these data suggest that such adjustments are not necessary for patients with renal impairment who are not receiving dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 25 publications
0
24
0
2
Order By: Relevance
“…In a small study of patients (N=22) treated with dalteparin, mean anti-Xa activity was similar between patients with renal impairment (mean C Cr, 26 mL/min; range, 16-38 mL/min) and those with normal renal function (C Cr >80 mL/min). 95 In a more recent study of prophylactic dalteparin in critically ill patients (N=138 evaluable) with severe renal impairment (C Cr <30 mL/min), no bioaccumulation was detected after a median of 7 days of prophylactic-dose dalteparin (5000 IU daily). 96 Treatment was not associated with excessive anticoagulation; peak anti-Xa levels were between 0.29 and 0.34 IU/mL.…”
Section: Therapies For Prophylaxis or Treatment Of Vte In Patients Wimentioning
confidence: 98%
“…In a small study of patients (N=22) treated with dalteparin, mean anti-Xa activity was similar between patients with renal impairment (mean C Cr, 26 mL/min; range, 16-38 mL/min) and those with normal renal function (C Cr >80 mL/min). 95 In a more recent study of prophylactic dalteparin in critically ill patients (N=138 evaluable) with severe renal impairment (C Cr <30 mL/min), no bioaccumulation was detected after a median of 7 days of prophylactic-dose dalteparin (5000 IU daily). 96 Treatment was not associated with excessive anticoagulation; peak anti-Xa levels were between 0.29 and 0.34 IU/mL.…”
Section: Therapies For Prophylaxis or Treatment Of Vte In Patients Wimentioning
confidence: 98%
“…Primary objectives were peak anti-Xa levels and adjusted anti-Xa levels, adjustment being carried out for dose and body weight. Results: A total of 42 patients could be analyzed during a median of 10 days (interquartile range IQR 4-13, range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In all groups, adjusted peak anti-Xa levels were not different on day 10 compared with day 1.…”
Section: )2mentioning
confidence: 99%
“…Tincani showed that no bioaccumulation occurred after 6 days of dalteparin prophylaxis, irrespective of renal function without major bleeding events. 28 Studies performed by both Schmid et al and Shprecher et al showed no increase in anti-factor Xa level in patients with renal impairment in prophylactic or therapeutic dosing, 10,29 and a metaanalysis from 2006 notes that insufficient data exist to assess risk for major bleeding for other LMWHs such as dalteparin and tinzaparin, while still advising adjusted dose enoxaparin in CKD. 30 Strengths.…”
Section: Discussionmentioning
confidence: 99%
“…9 A single study comparing 4-h postinjection anti-Xa levels in patients with a mean glomerular filtration rate (GFR) of 26.1 (range 16-38) ml/min versus normal renal function after therapeutic doses of dalteparin did not show any difference in the assay levels in those with impaired renal function when compared to those with normal renal function. 10 Currently, little is known about bleeding risks with therapeutic doses of dalteparin in patients with renal insufficiency, and guidelines regarding dose adjustments and preference of unfractionated heparin over dalteparin in this population are not sufficiently evidence-based. 11 To our knowledge, there has not been a prospective or retrospective study in which the bleeding risk of therapeutic dose of dalteparin in patients with renal insufficiency has been examined.…”
Section: Introductionmentioning
confidence: 99%